Hsp90 and FKBP51: complex regulators of psychiatric diseases. (4th December 2017) - Criado-Marrero, Marangelie; Rein, Theo; Binder, Elisabeth B.; Porter, James T.; Koren, John; Blair, Laura J.
Abstract : Mood disorders affect nearly a quarter of the world's population. Therefore, understanding the molecular mechanisms underlying these conditions is of great importance. FK-506 binding protein 5 ( FKBP5 ) encodes the FKBP51 protein, a heat shock protein 90 kDa (Hsp90) co-chaperone, and is a risk factor for several affective disorders. FKBP51, in coordination with Hsp90, regulates glucocorticoid receptor (GR) activity via a short negative feedback loop. This signalling pathway rapidly restores homeostasis in the hypothalamic–pituitary–adrenal (HPA) axis following stress. Expression of FKBP5 increases with age through reduced DNA methylation. High levels of FKBP51 are linked to GR resistance and reduced stress coping behaviour. Moreover, common allelic variants in the FKBP5 gene are associated with increased risk of developing affective disorders like anxiety, depression and post-traumatic stress disorder (PTSD). This review highlights the current understanding of the Hsp90 co-chaperone, FKBP5, in disease from both human and animal studies. In addition, FKBP5 genetic implications in the clinic involving life stress exposure, gender differences and treatment outcomes are discussed. This article is part of the theme issue 'Heat shock proteins as modulators and therapeutic targets of chronic disease: an integrated perspective'.